Dural enhancement and thickening in acute mastoiditis. Issue 2 (April 2015) - Shemesh, Shay; Marom, Tal; Raichman, Dominique Ben Ami; Tamir, Sharon Ovnat
Dural enhancement and thickening in imaging studies observed in acute mastoiditis patients is an uncommon phenomenon. It is infrequently seen in dural sinus thrombosis, and may be caused by infiltration of inflammatory cells and an increased number of thin-walled blood vessels. We present a three-year-old boy who presented with acute mastoiditis, complicated by subperiosteal abscess. Computerized tomography (CT) demonstrated subperiosteal abscess, and the child underwent mastoidectomy. Despite adequate treatment, symptoms worsened and neurological sequelae were suspected. CT and magnetic resonance imaging (MRI) studies demonstrated an atypical dural enhancement at the sigmoid perisinus and suboccipital abscess. The child underwent revision mastoidectomy and drainage of the abscess. Following the second procedure, resolution of symptoms was noted. Follow-up MRI did not demonstrate any dural pathologies.